(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
The development of coordination abilities is a fundamental aspect in the training of badminton players with hearing impairments, which determines their ability to adapt to rapidly changing game situations and perform technical and tactical techniques at a high level. The purpose of the research is to develop and experimentally substantiate the methodology of development of coordination abilities of badminton players with hearing impairments by using complexes of exercises from sports games. Participants: hearing impaired badminton players (n=14) aged 19-22 years old national team of Ukraine. The experiment took place during the period January 2024 - March 2024. At the beginning and at the end of the experiment, the coordination abilities of young badminton players were tested. Research methods: theoretical analysis and generalization of scientific and methodical literature; methods of testing physical abilities; mathematical and statistical methods; logical methods. Results: the experimental methodology for the development of coordination abilities of badminton players in sportsmen by means of sports games such as basketball and football, which included a combination of 6 different training complexes, as well as game practice in these sports, was developed. The results of 7 tests were found to be significantly improved in the experimental group: Romberg test, jumping rope in 1 min. and jumping to the error, test of speed reaction and coordination, test of reaction speed, bouncing a shuttlecock off the wall (p<0.05, p<0.01). In the control group, a statistically significant improvement was confirmed in only 3 tests. It was established that the application of the technique showed a significant positive influence on the level of development of coordination abilities of badminton players with hearing impairment. Thanks to the combination of exercises from different sports, the comprehensive development of key qualities necessary in badminton, such as agility and coordination, was achieved.